Indigenous and Local Communities Initiatives Have Transformative Potential to Guide Shifts Toward Sustainability in South America - Burgos-Ayala, A (SPRINGERNATURE, 2025)
Addressing current environmental crises requires a fundamental shift in our relationship with nature. Indigenous Peoples and Local Communities can guide diverse pathways towards sustainable and just futures, rooted in ancestral knowledge and relational values that challenge the status quo. Indigenous knowledge and practices, however, are still largely underappreciated, not being recognized as agents of transformative change. Inspired by the Seeds of Good Anthropocenes approach, this research identifies types of initiatives driven by Indigenous Peoples and Local Communities. Through hierarchical cluster analysis of 127 initiatives from Ecuador, Peru, and Colombia, six groups of initiatives are revealed. Three out of these six groups, i.e., Empowering, Reconnecting people and nature, and Intercultural and ancestral education (named here as I-Seeds), apply knowledge co-design processes led by Indigenous Peoples and Local Communities and have higher transformative potential. Such initiatives also implement amplification strategies of scaling deep that catalyze profound shifts in values and mindsets beyond the I-Seed. This study draws attention to the importance of Indigenous Peoples and Local Communities and their (retro)innovations to foster sustainability transformations.